GE_GERICHTE C/26176/2014 vom 22. Dezember 2015 - GE Cour de justice (2015)
PROTECTION DE L'UNION CONJUGALE; GARDE DE FAIT; VISITE; RELATIONS PERSONNELLES; OBLIGATION D'ENTRETIEN | CC.176; CC.285; CC.273